Implementation Triple Elimination Screening to Midwifes Knowledge About Risk Factors, Modes of Transmission and Impact of HIV, Syphilis, and Hepatitis B Type - Resi Galaupa; Fatma Oktavia; Ika Amelia; Siti Nur Ichlas; Tia Noviwarti (Postgraduate, University of Mataram, 2023)
Triple Elimination program that aims to early detection of HIV, syphilis and Hepatitis B infection in pregnant women and is very important for all pregnant women because it can save the lives of mothers and children. This type of research is observational research, namely by distributing questionnaires to determine the effect of the implementation of triple elimination on the knowledge of midwives in Palembang City. The results showed that of the 50 respondents who were old, around 19 people with a percentage (38.0%). While the young ones only reached 31 people (62.0%). The results showed that of the 50 respondents, the majority had a D3 education with a total of 36 people or (72.0%). While in S1 education reached 7 people (14.0%). And 7 people or (14.0%) professional education. The results of the analysis using the Chi Squre test, obtained a p-value of 0.000 on midwife knowledge, at age obtained a p-value of 0.285 and at education obtained a p-value of 0.0.019, which means greater than> 0.05, it can be interpreted that H0 is accepted and Ha is rejected. The conclusion is that there is a significant relationship between age, education and midwife knowledge in implementing triple elimination